Concrete Resistance in the Marine Environment: The Effect of Seawater Immersion (Curing) on Compressive Strength - Didik Setya Purwantoro; Muhammad Nur Fajar; Hasriadi Muchtar; Mohammad Aris; Wilis Sutiono (JACEE (Journal of Advanced Civil and Environmental Engineering), 2024)
Concrete is the most commonly used type of construction material but is affected by premature damage when exposed to the marine environment. The most common cause of damage is corrosion in the reinforcing steel. The problem that arises during the planning and construction stage of the beach safety building is the impact of seawater on the quality of the concrete we design. The research conducted is an experimental test with research in the laboratory by comparing the compressive strength value of normal concrete soaked in freshwater, saltwater in the laboratory and seawater in situ and the age of the used concrete is only 28 days. concrete that is immersed in seawater will experience a significant decrease in compressive strength value compared to normal concrete immersed in fresh water. For normal concrete soaked with seawater in the laboratory, the compressive strength value decreased from 29.96 MPa to 28.06 MPa. Meanwhile, concrete soaked in situ in seawater experienced a decrease in compressive strength value from 29.96 MPa to 25.55 MPa.